Prolegomena do polskich studiów nad wegetarianizmem w Rosji na przełomie XIX I XX wieku - Tymieniecka-Suchanek, Justyna (Studia Europaea Gnesnensia, 2019)
The article presents the origins and the early years of vegetarianism in Russia, as well as its turbulent development at the turn of the twentieth cen-tury, whilst taking into account the peculiarities of the Orthodox religious cul-ture and culinary customs. The author argues that strict fasting and the postu-lation of modest eating promoted the spread of the new fashion in Russian society.